Sydney Facial Nerve Clinic: experience of a multidisciplinary team. Issue 5 (4th March 2020) - Hayler, Raymond; Clark, Jonathan; Croxson, Glen; Coulson, Susan; Hussain, Gazi; Ngo, Quan; Ch'ng, Sydney; Low, Tsu‐Hui (Hubert)
Abstract: Background: The Sydney Facial Nerve Clinic (SFNC) is a multidisciplinary clinic established in 2015, consisting of surgeons (otolaryngologists, head and neck and plastics/reconstructive), physiotherapists and speech pathologists. Methods: We reviewed patients who attended the SFNC in the first 3 years and who had their symptoms recorded using the Facial Disability Index, and clinical staging recorded utilising the House–Brackmann (HB) score, Sydney Facial Nerve Score and Sunnybrook Facial Grading System (SFGS). Results: Between May 2015 and June 2018, 145 patients attended the clinic. Mean age was 44.6 ± 17.3 years with 94 (64.8%) females. Most referrals came from general practitioners ( n = 75, 54.5%). The most common aetiology was iatrogenic injury ( n = 55, 37.9%), followed by Bell's palsy ( n = 48, 33.1%), congenital ( n = 11, 7.6%), herpes zoster oticus ( n = 9, 6.2%), trauma ( n = 9, 6.2%) and other ( n = 13, 9.0%). The median HB was 4, the mean Sydney score 7.3/15 and the mean SFGS was 45/100. Patients with iatrogenic causes had the worse facial nerve scoring in HB, Sydney and SFGS. Patients with congenital aetiology reported the least symptoms on Facial Disability Index ( P < 0.001). Most patients were recommended non‐surgical management ( n = 92, 64.3%); 51 (35.7%) were referred for botulinum toxin + facial physiotherapy, 25 (17.2%) for physiotherapy alone, seven (4.9%) for botulinum toxin alone and nine (6.3%) for conservative management. Fifty‐one patients (35.7%) were recommended surgery, generating 75 procedures; 24 oculoprotective, 22 static, 12 gracilis transfers, 10 temporalis myoplasties and seven nerve transfers. Conclusion: Iatrogenic injuries are the most common presentation for this clinic and have a more severe clinical presentation. Most patients presenting to the SFNC were managed non‐surgically. Abstract : The Sydney Facial Nerve Clinic is a multidisciplinary clinic, dedicated to disorders of the facial nerve. We summarize the first 3 years of operation ( n = 145) and present the aetiology, severity and management of these patients.